PENINGKATAN KETERAMPILAN MENULIS SURAT MENGGUNAKAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING DI SEKOLAH DASAR - Zainudin, Zainudin; Halidjah, Siti; Margiati, K.Y (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe general problem, whether the use of approach to contextual teaching and learning can improve the writing skill of letter on students of grade V SDN 09 West Pontianak.This research aimed to improve students' writing skill of letter approach to contextual teaching and learningon students of grade V SDN 09 West Pontianak. The method used is descriptive method with class action research form. This study was conducted during V cycle with each cycle two time meeting. The results of the study design of the learning (RPP) of the cycle I is 3,32, the cycle II is 3.49 and, the cycle III is 3.8. The results of research from the implementation of learning from the cycle I is 3,13, the cycle II is 3.36, and the cycle III is 3,74. The result of research writing letter essay from cycle I that is 10,71, cycle II that is 11,67, and cycle III that is. So applying of contextual teaching and learning can improve letter writing skill students.Keywords: Writing Skills, Contextual Teaching and Learning